Students' experience of being seen by their physical education teachers and associated factors - Andresen, Fredrik; Torvik, Eli; Lagestad, Pål (Frontiers in Sports and Active Living, 2023)
Background The experience of being seen by physical education (PE) teachers is an important pedagogical term in school settings, and is closely related to the theory of recognition pedagogy and self-determination theory. However, very few studies have been conducted concerning this term, and extant research has typically been based on small sample sizes, and thus is unlikely to be extrapolated to other contexts. Purpose The aim of the study was to examine the extent to which students experience being seen by their PE teachers, which factors constitute the phenomenon of being seen as a pedagogical term, and how these factors correlate with students' experience of being seen by their PE teachers. This is the first study to identify factors that constitute the pedagogical term being seen, and uses a quantitative design. Method A questionnaire was developed on the basis of theory and previous research, and data from 412 students were collected. Principal component analysis was conducted to examine the dimensionality of the questions and which factors could be associated with being seen. From this, indexes were subsequently created for each factor. The association between these factors and the experience of being seen was determined using Spearman's correlation test. Results The results showed that 76.2% of the students reported being seen by the teacher in PE, while 7.8% reported not being seen, and 16.1% of the students neither disagreed nor agreed to being seen by the teacher in PE. The factor analysis indicated that being seen may be related to students' experience of the following: being able to display their skills; the teacher's caring behavior; feedback from the teacher; dialogue with the teacher; and evaluation and goals. The correlation analysis showed that these five factors correlated significantly at a medium level with the students' experience of being seen by their PE teacher. Conclusion The results point toward the importance of PE teachers giving their students opportunities to display their skills, providing the students with feedback through good dialogue, showing them that their teachers care, and involving students in evaluation and establishing goals in PE.